Reducing microbial contamination on wastewater-irrigated lettuce by cessation of irrigation before harvesting - Keraita, Bernard N.; Konradsen, Flemming; Drechsel, Pay; Abaidoo, Robert C. (Wiley, 2007)
Objective  To assess the effectiveness of cessation of irrigation before harvesting in reducing microbial contamination of lettuce irrigated with wastewater in urban vegetable farming in Ghana.Methods  Assessment was done under actual field conditions with urban vegetable farmers in Ghana. Trials were arranged in completely randomized block design and done both in the dry and wet seasons. Seven hundred and twenty‐six lettuce samples and 36 water samples were analysed for thermotolerant coliforms and helminth eggs.Results  On average, 0.65 log units for indicator thermotolerant coliforms and 0.4 helminth eggs per 100 g of lettuce were removed on each non‐irrigated day from lettuce in the dry season. This corresponded to a daily loss of 1.4 tonnes / ha of fresh weight of lettuce. As an input for exposure analysis to make risk estimates, the decay coefficient, k, for thermotolerant coliforms was 0.66 / day for the wet season and 1.49 / day for the dry season.Conclusion  In combination with other measures for improving water quality, the measure can significantly reduce faecal contamination of lettuce during the dry season. However, it is not suitable for the wet season due to unfavourable conditions for pathogen die‐off and re‐contamination by splashes from contaminated soils. The results provide a good basis for risk assessments and for devising more appropriate measures for risk reduction, especially in sub‐Saharan Africa.